Social Commitment in Writing - Gautam, Shreedhar (The Harvest, 2022)
Whether literature should include or exclude politics as its subject matter is a question over which opinions would widely differ. However, in this article an endeavour has been made to high light the literature written from the point of view of the socialist consciousness. A number of representative writers’ works are referred to as examples to show how they tried to connect literature with the contemporary events. The article concludes that literature while not fully socialist but sufficiently critical of class society will reveal important truths about the society and, thus, contribute to the freeing of the human consciousness from the limitations which class society has imposed on it.